2018
DOI: 10.2147/ott.s181706
|View full text |Cite
|
Sign up to set email alerts
|

miR-23b-3p and miR-130a-5p affect cell growth, migration and invasion by targeting CB1R via the Wnt/β-catenin signaling pathway in gastric carcinoma

Abstract: BackgroundGastric cancer (GC) is the most common malignancy and third leading cause of cancer mortality worldwide. The identification of a sensitive biomarker as well as effective therapeutic targets for the treatment of GC is of critical importance. microRNAs play significant roles in the development of cancer and may serve as promising therapeutic targets.MethodsThe mRNA and protein expression of CB1R were studied both in GC cells and tissues. GC cell lines with specific gene overexpression and knockdown vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 21 publications
5
33
0
Order By: Relevance
“…We also observed upregulation of miR-23b-3p, and similar to miR-181a-5p, this miRNA is also associated with several types of neoplasms [40][41][42][43][44]. Interestingly, the presence of miR-23b-3p in human urinary exosomes has been reported, and its expression was increased in urinary exosomes of patients with nephrotic syndrome [45].…”
Section: Discussionsupporting
confidence: 71%
“…We also observed upregulation of miR-23b-3p, and similar to miR-181a-5p, this miRNA is also associated with several types of neoplasms [40][41][42][43][44]. Interestingly, the presence of miR-23b-3p in human urinary exosomes has been reported, and its expression was increased in urinary exosomes of patients with nephrotic syndrome [45].…”
Section: Discussionsupporting
confidence: 71%
“…immunoreactivity was associated with disease severity and outcome in esophageal cancer (20), prostate cancer (44), pancreatic cancer (45), ovarian cancer (46) and others. Furthermore, CNR1 knockout mice developed smaller and fewer tumors in a diethylnitrosamine induced hepatocellular carcinoma model (15), and overexpression of CNR1 in esophageal squamous cell carcinoma and gastric cancer revealed that CNR1 activation could promote cell proliferation and invasion (20,47). In this study, although TCGA data showed that the expression of CNR1 mRNA was downregulated in HNSCC compared with normal samples, CNR1 mRNA was highly expressed in HPV positive HNSCC compared with HPV negative HNSCC (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Additionally, miR-130a was demonstrated to be upregulated by hypoxia in gastric cells, also targeting RUNX3 and therefore increasing -in combination with miR-495cell proliferation while lowering apoptosis [34]. These interactions may also be exerted via the Wnt/β-Catenin signalling pathway, as this axis was demonstrated to be active in gastric cancer cells [35]. Together, these data point towards a regulative role of miR-130a during the early phase of several differentiation processes.…”
Section: Discussionmentioning
confidence: 84%